2017
DOI: 10.1016/j.ebiom.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death - Ligand 1 Expression Distinguishes Invasive Encapsulated Follicular Variant of Papillary Thyroid Carcinoma from Noninvasive Follicular Thyroid Neoplasm with Papillary-like Nuclear Features

Abstract: BackgroundThe noninvasive Encapsulated follicular variant of papillary thyroid cancer (EFVPTC) has been reclassified as Noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) without a significant risk for malignant behavior. However the evaluation remains a challenge for clinicians. We sought to determine whether programmed death-ligand 1 (PD-L1) expression may serve as a biomarker to predict invasiveness of EFVPTC and assist to distinguish these neoplasms from NIFTP.MethodsImmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 25 publications
4
59
0
Order By: Relevance
“…As reported in previous histologic series, we compared PD‐L1 (cytologic and histologic) expression with matched thyroid staging according to the eighth edition of the AJCC Cancer Staging Manual in the 113 malignant cases of our series. The data showed that the majority of patients (n = 105; 93%) had stage I disease, 6 had stage II disease (5.3%), 1 had stage III disease, and 1 other had stage IV disease (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in previous histologic series, we compared PD‐L1 (cytologic and histologic) expression with matched thyroid staging according to the eighth edition of the AJCC Cancer Staging Manual in the 113 malignant cases of our series. The data showed that the majority of patients (n = 105; 93%) had stage I disease, 6 had stage II disease (5.3%), 1 had stage III disease, and 1 other had stage IV disease (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…PD‐L1 expression was evaluated using the tumor proportion score system as the percentage of viable tumor cells showing either partial or complete membranous and cytoplasmic positivity. According to the literature, PD‐L1 in papillary thyroid carcinoma (PTC) has shown increased expression (using the E1L3N antibody; Cell Signaling Technology, Inc) with both plasma membrane and cytoplasm localization . In our series, ICC was carried out using the Dako 22C3 clone, which resulted in both cytoplasmic and membranous PD‐L1 staining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maletta et al [7] assessed CD56 immunohistochemical expression in cytological samples of NIFTP and described a heterogeneous intermediate expression between follicular benign lesions and invasive PTC. Fu et al [19] found that PDL-1 immunohistochemical expression in histological samples was higher in infiltrative lesions than in NIFTP. As for molecular studies, NIFTP were supposed to be clonal lesions and, therefore, neoplastic [2].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Rosenbaum et al on poorly differentiated thyroid carcinoma (PDTC) also supports the concept that PD‐L1 staining is often limited, focal, and heterogeneous, limiting its use as a diagnostic marker . Fu et al analyzed the expression of PD‐L1 in 52 NIFTPs, 45 invasive encapsulated follicular variants of PTC (EFVPTCs), and 40 benign nodules . They found no significant differences in PD‐L1 cytoplasmic staining between NIFTPs and benign lesions, whereas there was a significant increase in invasive EFVPTCs.…”
Section: Pd‐l1 Expression and Thyroid Cancer Diagnosismentioning
confidence: 91%